YAP-associated chromosomal instability and cholangiocarcinoma in mice - Ilyas, Sumera I; Fischbach, Samantha R; Bronk, Steven F; Hirsova, Petra; Krishnan, Anuradha; Dhanasekaran, Renumathy; Smadbeck, James B; Smoot, Rory L; Vasmatzis, George; Gores, Gregory J (Oncotarget, 2018)
Deregulated Hippo pathway signaling is associated with aberrant activation of the downstream effector yes-associated protein (YAP), an emerging key oncogenic mediator in cholangiocarcinoma (CCA). In our prior work, we have demonstrated that biliary transduction of YAP along with Akt as a permissive factor induces CCA in mice. To further delineate the mechanisms associated with YAP-associated biliary oncogenesis, we have established seven malignant murine cell lines from our YAP-driven murine CCA model. These cells express the CCA markers SRY (Sex Determining Region Y)-Box 9 (SOX9), cytokeratin (CK)-7 and 19 but lack hepatocyte nuclear factor 4 alpha and alpha-smooth muscle actin, markers of hepatocellular carcinoma and cancer-associated fibroblasts, respectively. Notably, the murine CCA cells can be readily implanted into mouse livers with resultant orthotopic tumor formation. In this unique syngeneic orthotopic murine model, tumors exhibit histopathologic features resembling human CCA. We analyzed transcriptome data from YAP-associated parent CCA tumor nodules and identified a gene expression pattern associated with chromosomal instability, known as CIN25. Similarly, mate-pair sequencing of the murine CCA cells revealed chromosomal missegregation with gains and losses of several whole chromosomes demonstrating aneuploidy. Of the CIN25 genes, forkhead box M1 (Foxm1), a key cell cycle regulator, was the most significantly upregulated CIN25 gene product. Accordingly, small interfering RNA (siRNA)-mediated silencing of YAP as well as FOXM1 inhibition with thiostrepton induced CCA cell death. These preclinical data imply a role for YAP-mediated chromosomal instability in cholangiocarcinoma, and suggest FOXM1 inhibition as a therapeutic target for CCA.
Keywords: chromosomal instability; mate-pair sequencing; SB cell lines; FOXM1